Understanding the Integrative Model of the European Union While Exploring the Nexus between Populism and Democracy - Bano, Nusrat; Khan, Abdul Basit; Ashraf, Muhammad Javed (Annals of Human and Social Sciences, 2024)
The European Union (EU) has been a symbol of unity in diversity which provides for a model of collective functioning of various countries while preserving their distinct identity. The historical factors leading to this integration might vary in the case of every member country but the fact goes un-denied that the model has continuously been manifesting successful functioning nevertheless the general public belonging to various member countries had different conceptions and feelings towards this integrative model. Besides, democracy has been the main spirit in strengthening the body politic of western countries which, on its part, accommodates diversity of opinions, feelings and beliefs pertaining to the society at large. In that perspective, it has recently been observed that the European people are in a moral battle against the “elite” culture and the populist ideology and its association with modern democracies have gained considerable attention therein. The main aim of this research is to identify how populism affects different models of democracies in Europe and whether or not it poses any threat to European integration. The study also examines populism under the theoretical lenses of neoliberalism and neorealism to analyze that to what extent nature of political parties and their ideologies in most of European countries play role for integration or otherwise of the Union. It concludes that because of the ever-accommodating nature of European democratic culture, these movements are not posing any considerable threat to the Union for the time being.